Specificity of Russian Teenager's Civic Identity (Case of Campers at the Artek International Children's Centre) - Elena V. Belovol; Sergey V. Melkov; Tatiana N. Sakharova (National Research Mordova State University, 2022)
Introduction. Russian psychology is gaining deeper awareness of the problem of defining the content of civic identity and diagnosing its components, the understanding of which is a precondition for its formation in the context of the key objectives of Russian education. The relevance of the research is determined by the public and scientific significance of the problem of civic identity formation, as the level of its formation is the basis for further development and prosperity of Russia. The objective of the article is to present the results of empirical study of the peculiarities of civic identity of modern Russian adolescents. Materials and Methods.The empirical part of the study involved 640 respondents, adolescents aged 15-17. In order to diagnose the degree of formation of adolescentsʼ civic identity and to study its structure, the authorʼs questionnaire "Personal civic identity profileˮ was used. To analyse the level of formation and structure of adolescentsʼ civic identity, a set of methods for mathematical data processing was used. Results. The study showed a satisfactory level of civic identity formation among modern adolescents. At the same time, a certain asynchrony in the formation of the various components of civic identity was observed. The study of the degree of formation of civic identity of an individual determined its high level in the studied sample. The analysis of individual components of the internal position of the individual as a basis for the formation of civic identity indicates that teenagers have the most developed value attitude towards themselves. Adolescents are not yet aware of the value of others while recognising the value of the surrounding reality. The gender of the respondents has no significant impact on the level of formation of civic identity or on the components of person's inner position. Discussion and Conclusion. The results of the study contribute to the development of ideas about the psychological components of civic identity and their formation in modern Russian adolescents. The material in this article can be used in applied developments in the formation of civic identity, in organizing educational work in schools, and in training and retraining teaching staff who are capable of effectively carrying out educational work aimed at forming a pupil's civic identity.